Tradisi Seren Taun berbasis Kearifan Lokal Masyarakat AdatKasepuhan (Suatu Kajian Holistik Antropologi Hukum) - Emy Handayan; Endang Sumiarm; Dominikus Rato; Sekhar Candra; Yustika Niken Sharaningtyas (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2024)
Seren Taun is a series of agricultural activities carried out every year by a traditional community in atraditional area which is usually called a traditional traditional ritual, as a form of respect for the ancestors andthe Goddess Sri with all forms of rituals and cultural arts performances of the Kasepuhan indigenouscommunity from very from long ago to modern art displayed by indigenous peoples. The rice was brought,paraded, accompanied by everyone present to be stored in the Leuit Si Jimat communal barn. The local wisdomof the Kasepuhan traditional community of Banten Kidul is a community that still upholds and carries outtraditions with the supervision of the Abah as the Traditional Leader. Kasepuhan residents are devoutfollowers of the Islamic religion, but in their daily lives they are characterized by mythical and animist beliefsor they still maintain ancestral beliefs such as burning incense, giving offerings, traditional ceremonies, placingfences on doors, and other ancestral beliefs. The Holistic Study of Legal Anthropology illustrates that traditionalrituals based on local wisdom are a manifestation of the behavior or actions of indigenous people in an effort toget closer to God. Because rituals are ceremonies carried out by indigenous people throughout their lifetime,they are carried out by every indigenous community in their traditional territory, because they are ceremoniesfor the life cycle of an individual's life as a member of society (the universal circle of life).Keywords: Seren Taun Tradition, Local Wisdom of the Kasepuhan Indigenous Community, Holistic Study ofLegal Anthropology